[Probe Team's 5th anniversary special Elections [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Features the 1992 election campaigns and voting.
VHS.
Keywords: Public opinion -- Philippines; Elections -- Philippines; Presidents -- Elections -- 1882. -- Philippines